Evaluation of central nervous system depressant activity of methanolic and petroleum ether extract of Manilkara zapota leaves (in vivo) - Manirujjaman; Trudi Collet (International Journal of Phytomedicine, 2016)
The purpose of this study was to examine the central nervous system (CNS) -depressant activity of methanolic and petroleum ether extracts of leaves obtained from Manilkara zapota (Sapotaceae) in vivo. CNS-depressant action was evaluated by observing the effects of plant extracts on both exploratory and spontaneous locomotor activity in mice using open field and hole cross tests respectively. The extracts were found to exhibit CNS-depressant activity in a dose-dependent manner. In the open field test, both the methanolic and petroleum ether extracts reduced the exploratory behavior of mice significantly (p<0.05). Although the extracts reduced locomotor activity in the hole cross test, the results were found to be insignificant. Overall, these findings indicate that both types of extracts derived from M. zapota leaves possess CNS-depressant activity.